Ekonomi Islam sebagai Paradigma Transformatif: Pendekatan Interdisipliner dan Multidisipliner - Fitri Yenti; Hospi Burda; Jasri Waldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Background. This study is motivated by growing concerns over the limitations of contemporary economic systems in addressing global challenges such as social inequality, moral degradation in economic practices, environmental crises, and weak institutional governance. Purpose. The purpose of this study is to explore how Islamic economics can critically respond to global challenges, including social inequality, the moral crisis of capitalism, environmental degradation, and weaknesses in institutional governance. Method. The study employs a qualitative–conceptual methodology based on library research, drawing on critical analyses of classical and contemporary literature in Islamic economics, sociology, psychology, law, philosophy, political economy, environmental studies, and history. Data are analyzed using a descriptive–analytical method with an emphasis on epistemological and conceptual frameworks.. Results. The results demonstrate that an interdisciplinary approach enables Islamic economics to move beyond a narrow normative–legal orientation toward a more comprehensive framework that integrates ethical values, empirical analysis, and context-sensitive policy considerations. Conclusion. The findings also indicate that maqāṣid al-sharīʿah functions not merely as a normative reference but as a critical evaluative instrument for aligning economic practices with broader objectives of justice, sustainability, and human well-being. In conclusion, Islamic economics emerges as a holistic and transformative paradigm capable of offering ethically grounded and sustainable solutions to contemporary global economic challenges, provided it is supported by methodological rigor and institutional coherence